Sosialisasi Komersialisasi Pengembangan Hasil Riset Produk Kesehatan Dosen Fakultas Kedokteran Unjani - Jayanti, Dwi; Maryani, Neni; Romli, Romli; Dzaky, Vicky; Marlina (Fakultas Teknik Universitas Lancang Kuning, 2022)
Abstract Currently, there are many research results conducted by researchers in the health sector which actually have tremendous potential if commercialized properly. However, limited knowledge related to the commercialization of health products made in the end many research results did not develop, especially at the Unjani Faculty of Medicine. One of the efforts to overcome this problem, the method used is to conduct online socialization (webinar) regarding business feasibility studies, cost of production and determination of selling prices with the aim of providing understanding to research lecturers in the health sector in order to develop their research results. Through the webinar activity, the results obtained are that there is a fairly good understanding of the webinar participants regarding business feasibility studies, calculating the cost of production and determining selling prices.